Suppose we want to estimate $\int_0^{h}f(x) dx$ using Lagrangian interpolating polynomials and with nodes $x_0 = 0,x_1 = \frac{2}{3}h$. Thus we compute the quadrature rule

$$ Q(f) = a_0f(0)+a_1f(\frac{2}{3}h). $$

Now using the fact that $$ a_k = \int_0^hl_k(x)dx $$

we can find $$ Q(f) = \frac{h}{4}(f(0)+3f(\frac{2}{3}h)). $$

Then here comes the part where I get confused. We are then asked to find the composite quadrature rule for $\int_0^1f(x)dx$ and use it to estimate $\int_0^1 \cos(x)dx$ using a step size $h=0.5$.

I am not so sure how to proceed from here. Cheers in advance for any help.


Split the interval $[0,1]$ into two $[0,1/2)\cup [1/2,1]$, so that

$$ \int_0^1{\rm d}x~f(x) = \int_0^{1/2}{\rm d}x~f(x) + \int_{1/2}^1{\rm d}x~f(x) = \int_0^{h}{\rm d}x~f(x) + \int_{h}^{2h}{\rm d}x~f(x) \tag{1} $$

with $h=1/2$. The second integral in the "problematic" one, to solve it, use the change of variables $y = x - h$, ${\rm d}x = {\rm d}y$ it then becomes

$$ \int_0^1{\rm d}x~f(x) = \int_0^{h}{\rm d}x~f(x) + \int_{0}^{h}{\rm d}y~f(y + h) \tag{2} $$

Now both integrals can be approximated with the rule you described. In both cases $f(x) = \cos(x)$, so that $\cos(y+h) = \cos(y + 1/2)$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.